2023
DOI: 10.1039/d3ta01265d
|View full text |Cite
|
Sign up to set email alerts
|

Nanoflower-like MoS2 anchored on electrospun carbon nanofiber-interpenetrated reduced graphene oxide as a microbial fuel cell anode achieving high power density

Abstract: Weak biofilm habitation and sluggish extracellular electron transfer (EET) between the biofilm and anode are major obstacles to achieving a high power density in microbial fuel cells (MFCs). Tailoring the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…These differences can be partially attributed to the volatilization of PVP during the pyrolysis process, which formed N-containing reactive species that can etch the surface of the CNFs. 23,30 Additionally, the introduction of S could also induce the formation of defective structures on the CNFs, leading to a rough surface. 31 The FeS/Fe 3 C@NCNFs/rGO aerogel (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences can be partially attributed to the volatilization of PVP during the pyrolysis process, which formed N-containing reactive species that can etch the surface of the CNFs. 23,30 Additionally, the introduction of S could also induce the formation of defective structures on the CNFs, leading to a rough surface. 31 The FeS/Fe 3 C@NCNFs/rGO aerogel (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was worth noting that the FeS/Fe 3 C@NCNFs/rGO-modified anode revealed the highest specific capacitance of 31.71 mF cm −2 , which was significantly higher than that of FeS/Fe 3 C@NCNFs (6.38 mF cm −2 ), NCNFs (1.74 mF cm −2 ) and pristine CC (0.29 mF cm −2 ) anodes. The high specific capacitance indicated that more electrons can be stored in the materials leading to a stronger current response, 2,30,36 which can be attributed to the abundant active sites on the surfaces of the Fe, N, and S co-doped CNFs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of carbon-based materials and transition-metal-based materials has also been demonstrated to be an effective strategy for performance enhancement of MFCs. 12,16–18 Liu et al 25 designed a three-dimensional composite structure (rGO/CNF@MoS 2 ) as an anodic electrocatalyst of MFCs, which consisted of carbon nanofibers and reduced graphene oxide (rGO) with uniformly loaded MoS 2 nanoflowers. This MFC with an rGO/CNF@MoS 2 anode achieved an impressive power density of 3584 mW m −2 , which was mainly attributed to the huge specific surface area provided by the three-dimensional structure.…”
Section: Introductionmentioning
confidence: 99%
“…4–6 In MFCs, anodes are attached by microorganisms that generate electrons by oxidatively decomposing organic compounds in wastewater, while cathodes accept the electrons through the oxygen reduction reaction (ORR) of oxygen on the air cathode. 7,8 The power density of currently available MFCs is limited by slow anode and cathode reaction kinetics, which have been attracting much research interest. 9–12 On the cathode, there are two paths for the ORR to take place.…”
Section: Introductionmentioning
confidence: 99%